(untitled) (Journal of the College of Basic Education, 2022)
The study included 24 patients compared to 16 healthy subjects. The results showed a significant increase in the level of white blood cells (10) among the infected (148.75 ± 13.14 pg / ml) compared to healthy subjects (96.68) ± 4.14 pg / ml. 10e6 / ul 3.68 ± 21 0.) compared to healthy subjects (10e6 / ul 4.64 ± 0.17) and a decrease in hemoglobin in the infected (10.54 ± 0.22 g / dl) compared to healthy subjects (11.34 ± 0.19 g / dl) and a decrease in the pressure of red blood cells (PCV) in children The injured (32.44 ± 0.49) compared to the healthy (35.47 ± 0.17). From this we conclude that leukopenia 10 has a major role in the immune response against histolytic amoebiasis, as well as that histolytic amoebiasis affects the level of RBC, Hb, and PCV.